Peningkatan Anggaran Persenjataan Militer China sebagai Bagian dari Security Dilemma di Kawasan Asia Pasifik - Rezki Satris (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : The increase in Chinese military spending from year to year is part of security dilemma in Asia Pacific region. Such increase in defense and military spending of China indicates its concern (security dilemma) to regional countries like Japan. In addition, to maintain hegemony as a country that has influence in region as well as the fragility of regional conflict requires China to strengthen its military defense system. Security dilemma affects countries in the world and put them in the shadow of fear. Assumption that is built within security dilemma is that the world is in anarchist position. China has been undergoing significant change after the cold war in global dan regional security diplomacy that is based on perspective that view threats and opportunities arising from international structure in general, and regional structure specifically. Therefore, China began to formulate policies that pay attention to the future security and prosperity of his country.Keywords: security dilemma, military spending, international security